Metal content and P-T evolution of CO2-bearing ore-forming fluids of the Haftcheshmeh Cu-Mo porphyry deposit, NW Iran. (1st April 2020) - Zaheri-Abdehvand, N.; Tarantola, A.; Rasa, I.; Hassanpour, S.; Peiffert, C.
Highlights: The Haftcheshmeh Cu-Mo porphyry deposit formed from H2 O-NaCl-CO2 hydrothermal fluids. Fluid inclusions record repeated CO2 fluxes and fluid boiling. Fluid inclusions have elevated Na, K, Fe, Mn, Cu and Mo content. Molybdenite precipitation predates chalcopyrite. Lithostatic to hydrostatic metal deposition occurred at 450–250 °C and 3.0–1.0 km. Abstract: The Haftcheshmeh Cu-Mo porphyry deposit is located in the NW part of the Arasbaran Metallogenic-Magmatic Zone, NW Iran. Ore mineralisation is generally hosted within the gabbro-diorite and granodiorite porphyry stocks, presenting various types of hydrothermal quartz veins and veinlets associated with potassic to sericitic alteration. Stage I corresponds to barren quartz-K-feldspar-biotite-anhydrite veins (A veins), with minor metal sulphides (pyrite ± chalcopyrite), surrounded by K-feldspar and biotite halos related to potassic alteration. Stage II is described with quartz-molybdenite-chalcopyrite-pyrite-bornite-magnetite-hematite-biotite veins, predominantly occurring in the potassic alteration halos (B veins). Stage III shows pyrite-quartz-chalcopyrite ± molybdenite-galena-sphalerite associated with sericitic alteration halos (D veins). The coexistence of halite-saturated aqueous-rich and low-salinity vapour-rich fluid inclusions in the H2 O-NaCl-CO2 system is evidence of fluid boiling in each alteration/mineralising stage. This process was subsequently followed by meteoric water input diluting the CO2 -bearing ore-forming fluid. LA-ICPMS data of fluid inclusions associated with the successive stages reveal elevated Na, K, Fe, Mn, Cu and Mo content. The metal content of fluid inclusions of Stages II and III is in large part due to accidentally trapped minerals. Molybdenite and chalcopyrite started precipitating between stages I and II from a metal-poor fluid. The long-duration (>1 Ma) of the magmatic-hydrothermal activity and associated CO2 fluxes and repeated fluid boiling events lead to ore deposition at temperatures of 450 to 250 °C and at depths between 3.0 and 1.0 km from near-lithostatic to near-hydrostatic conditions.